Effects of cuff size and position on the agreement between arterial blood pressure measured by Doppler ultrasound and through a dorsal pedal artery catheter in anesthetized cats - Cerejo, Sofia A. [UNESP]; Teixeira-Neto, Francisco J. [UNESP]; Garofalo, Natache A. [UNESP]; Pimenta, Eutálio LM.; Zanuzzo, Felipe S. [UNESP]; Klein, Adriana V. [UNESP] (Elsevier, 2020)
Objective: To compare the effects of cuff size/position on the agreement between arterial blood pressure measured by Doppler ultrasound (ABPDoppler) and dorsal pedal artery catheter measurements of systolic (SAPinvasive) and mean arterial pressure (MAPinvasive) in anesthetized cats. Study design: Prospective study. Animals: A total of eight cats (3.0–3.8 kg) for neutering. Methods: During isoflurane anesthesia, before surgery, changes in end-tidal isoflurane concentrations and/or administration of dopamine were performed to achieve SAPinvasive within 60–150 mmHg. Cuff sizes 1, 2 and 3 (bladder width: 20, 25 and 35 mm, respectively) were placed on distal third of the antebrachium, above the tarsus and below the tarsus for ABPDoppler measurements. Agreement between ABPDoppler and SAPinvasive or between ABPDoppler and MAPinvasive was compared with reference standards for noninvasive blood pressure devices used in humans and small animals. Results: Mean bias and precision (±standard deviation) between ABPDoppler and SAPinvasive met veterinary standards (≤10 ± 15 mmHg), but not human standards (≤5 ± 8 mmHg), with cuffs 1 and 2 placed on the thoracic limb (7.4 ± 13.9 and –5.8 ± 9.5 mmHg, respectively), and with cuff 2 placed proximal to the tarsus (7.2 ± 12.4 mmHg). Cuff width-to-limb circumference ratios resulting in acceptable agreement between ABPDoppler and SAPinvasive were 0.31 ± 0.04 (cuff 1) and 0.42 ± 0.05 (cuff 2) on the thoracic limb, and 0.43 ± 0.05 (cuff 2) above the tarsus. ABPDoppler showed no acceptable agreement with MAPinvasive by any reference standard. Conclusions and clinical relevance: The agreement between ABPDoppler and SAPinvasive can be optimized by placing the occlusive cuff on the distal third of the antebrachium and above the tarsus. In these locations, cuff width should approach 40% of limb circumference to provide clinically acceptable estimations of SAPinvasive. Doppler ultrasound cannot be used to estimate MAPinvasive in cats.
Keywords: cats; Doppler; noninvasive blood pressure